Establishing a System for Testing Replication Inhibition of the Vibrio cholerae Secondary Chromosome in Escherichia coli - Schallopp, Nadine (Antibiotics (Basel), 2017)
Regulators of DNA replication in bacteria are an attractive target for new antibiotics, as not only is replication essential for cell viability, but its underlying mechanisms also differ from those operating in eukaryotes. The genetic information of most bacteria is encoded on a single chromosome, but about 10% of species carry a split genome spanning multiple chromosomes. The best studied bacterium in this context is the human pathogen Vibrio cholerae, with a primary chromosome (Chr1) of 3 M bps, and a secondary one (Chr2) of about 1 M bps. Replication of Chr2 is under control of a unique mechanism, presenting a potential target in the development of V. cholerae-specific antibiotics. A common challenge in such endeavors is whether the effects of candidate chemicals can be focused on specific mechanisms, such as DNA replication. To test the specificity of antimicrobial substances independent of other features of the V. cholerae cell for the replication mechanism of the V. cholerae secondary chromosome, we establish the replication machinery in the heterologous E. coli system. We characterize an E. coli strain in which chromosomal replication is driven by the replication origin of V. cholerae Chr2. Surprisingly, the E. coli ori2 strain was not inhibited by vibrepin, previously found to inhibit ori2-based replication.